Decision framework for ocean thermal energy plant site selection from a sustainability perspective: The case of China. (10th July 2019) - Zhang, Jinying; Xu, Chuanbo; Song, Zixin; Huang, Yong; Wu, Yunna
Abstract: Site selection is a key factor to the success of ocean thermal energy conversion (OTEC) project. It is a multi-criteria decision making (MCDM) problem with a series of conflicting criteria involved. However, limited studies were found concerning this area and problems existing in classical MCDM methods tended to fail OTEC site selection decisions. Therefore, this paper proposes an extended MCDM method and establishes a new decision-making framework to select the optimal location. First, a comprehensive evaluation criteria system for OTEC site selection from the view of sustainability with 16 criteria involved is established. Second, feasible alternative sites for OTEC project are identified by PEST analysis. Third, an extended PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) under intuitionistic fuzzy environment is proposed to avoid compensation assumptions. During the decision process, seven groups of experts shared the work and cooperated with each other according to their backgrounds. Finally, a real case is studied and sensitive analysis is conducted, demonstrating the robustness and effectiveness of the proposed method. This study can effectively improve OTEC site selection decision making quality and also extends the domains of intuitionistic fuzzy PROMETHEE applications. Highlights: A novel multi-criteria decision-making framework for site selection is proposed. The criteria system for ocean thermal energy conversion site selection is constructed. A case study is carried out in areas of Guangdong and Guangxi Provinces in China.